The Contribution of Foreign Radio Stations to Nation’s Struggle for Freedom during the Years of Soviet Regime - Bagušauskas, Juozapas Romualdas (Genocidas ir rezistencija, 2001)
Extending activities of fights for freedom, resistance organisation initiated broadcasts of programmes in Lithuanian by radio stations abroad. As a result, the Voice of America started its programmes as early as February 16, 1951 and the radio of Rome on May 4,1952. In 1951 they were transmitted on 26 frequencies per day. For consolidation of Lithuanians abroad programmes were broadcasted both in Lithuanian and in the language of the country they resided.Soviet ideological structures took counter-measures against the words of truth by launching mass radio interference, followed by other means of terror. The process lasted till the 90-ies. Its character reflected changes in home and foreign policy of the SSRS in certain historic periods. During the last years of Soviet regime, the SSRS employed well over 3 thousand transmitters with power total to 600 thousand kilowatts for the interference purpose.Broadcasted radio programmes were focussed on the issue of Lithuania's statehood and condemnation of Soviet occupation and annexation. They also disclosed and explained the ways the Soviet propaganda justified the destroy of statehood, like: class struggle; biased interpretation of certain historic events (occupation issue in particular); and teachings on the advantages of Soviet Lithuania's stability. Disintegration of colonial system throughout the world brought about the issue of Soviet neocolonialism and its denouncement. The Voices had estimated economic, social and political relations in occupied Lithuania as the manifestation of Soviet neo- colonial policy, supporting their evidence with economic and political analyses.The idea that aspirations of freedom will come true, that the communist system shall inevitably collapse, and Lithuania sooner or later will peacefully restore the lost statehood, provided by favourable historical situation, had never died throughout the existence of radio world services for Lithuania.
Keywords: propaganda; emigree; USA; antisoviet resistance; foreign radio